Estimasi Biaya Konseptual Pada Jembatan Beton Bertulang Dengan Metode Indek Biaya - Bagyo Mulyono; Paulus Setyo Nugroho (Dinamika Rekayasa, 2017)
Cost estimation is the art of estimating the amount of cost required for an activity based on available information. The conceptual cost estimate is an early stage in planning a construction project. This estimate provides the cost that must be budgeted for a construction project. Cost conceptual estimates have low accuracy because the time of calculation and available information is limited. This study aims to obtain a conceptual model of the conceptual cost of short-spaced bridges. The method used is the cost index. The cost index is a figure indicating the cost per m2 of bridges at a given time. The required data are contract documents and drawings design that are built in 2012 - 2015 in Banyumas residency area. Span of bridge 4 - 38.8 meters and width of bridge 2 - 7 meters with caisson  foundation. The data were obtained from Dinas Bina Marga and Public Works Agency. The results showed that the conceptual cost model of reinforced concrete bridge with caisson foundation was BJiL = (100.540.56t2-404.528.636,58t + 406.914.286.088,58) x P x W, with t = year, P = span bridge, and W = bridge width. The error value of validation of this model is 2.31%.